Using the analytical calculation method for cooling systems studying - Slabospitsky, R.P.; Khazhmuradov, M.A.; Lukyanova, V.P.; Prokhorets, S.I. (Вопросы атомной науки и техники, 2013)
An analytical method for calculating the air flow battery cooling with non-uniform heat distribution in the battery cells is considered. The calculations were done for different air rates and directions. It is shown that to ensure the normal battery operation the air flow rates must be greater than 2 m/s.